Internal audit tool for minimizing the risk of fraud - Elçzbieta Klamut (e-Finanse: Financial Internet Quarterly, 2018)
The purpose of the article is to analyze the relevance of the audit in minimizing the risk of fraud. The methodology of the research: literature analysis, internal audit research and questionnaires for the selected group of companies were carried out for the purpose of the article. The result: internal audit of micro-enterprises is implemented sporadically, so it is difficult to talk about its effectiveness, while in other entities it fulfills its role, provided it is properly carried out, which means while maintaining its independence and impartiality.
Keywords: M42; G32; 330; management; risk; internal audit; business transactions